Longitudinal study of obesity in the National Survey of Health and Development. Issue 6283 (4th July 1981) - Stark, O; Atkins, E; Wolff, O H; Douglas, J W
Abstract : In a nationally representative cohort of 5362 children born in one week in March 1946 weights and heights were recorded at 6, 7, 11, 14, 20, and 26 years. Overweight was defined as a weight that exceeded the standard weight for height, age, and sex by more than 20% (relative weight greater than 120%). The prevalence of overweight was 1.7% and 2.9% in boys and girls respectively at 6 years; 2.0% and 3.8% at 7 years; 6.4% and 9.6% at 11 years; 6.5% and 9.6% at 14 years; 5.4% and 6.5% at 20 years; and 12.3% and 11.2% at 26 years. The risk of being overweight in adulthood was related to the degree of overweight in childhood and was about four in 10 for overweight 7-year-olds. Analysis of the data in the reverse direction showed that 7% and 13% respectively of 26-year-old overweight men and women had been overweight at the age of 7. These results suggest that there is no optimal age during childhood for the prediction of overweight in adult life and that excessive weight gain may begin at any time. Overweight children are more likely to remain overweight than their contemporaries of normal weight are to become overweight.